Model Pertumbuhan Polinomial Tanaman Sengon (Paraserianthes falcataria (L) Nielsen) di Lahan Rawa Gambut, Kalimantan Tengah: Polynomial Growth Model of Sengon Plant (Paraserianthes falcataria (L) Nielsen) in Peat Swamp, Central Kalimantan - Wahyudi Wahyudi; Yetrie Ludang; Yaesar Wawan (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2021)
Sengon (Paraserinthes falcataria (L) Nielsen) is a fast-growing plant that is widely cultivated by people in dry land. Currently, the cultivation of this plant is also mostly carried out on unflooded peat swamp land in Central Kalimantan. Utilization of peat swamp land has good prospects because this land is rich in organic matter as a source of plant nutrition. This study aims to determine the growth of sengon plants and create a plant growth model to predict the diameter and height of plants at a certain age. The research was conducted in Pulang Pisau Regency, Central Kalimantan Province. The model used to predict the growth of sengon plants is a polynomial equation. The results showed that the growth of sengon plants planted in unflooded peat swamp land at the ages of 6, 13, 30, 36, 48, and 56 months namely 3.76 cm; 7.07 cm; 12.94 cm; 13.91 cm; 18.76 cm; and 22.88 cm respectively for diameter (dbh); 4.64 m; 9.70 m; 11.45 m; 12.16 m; 14.75 m; and 15.20 m respectively for shoot height; and 2.37 m; 4.13 m; 4.85 m; 5.28 m; 5.62 m; and 6.21 m respectively for branch-free height. Sengon plant growth model with polynomial equations is y = -0.01802 + 0.739x - 0.0157x2 + 0.0002X3; y= 0.6002 + 0.893x - 0.0236x2 + 0.0002x3; and y = 0.5676 + 0.3777x - 0.0106x2 + 0.0001x3 for diameter (dbh), shoot height and branch-free height, respectively. The equation is valid and has high accuracy so that it can be used to predict diameter, shoot height and branch-free height of sengon plants until the age of 56 months.